Effectiveness and safety of regimens containing linezolid for treatment of Mycobacterium abscessus pulmonary Disease - Li-ping Cheng; Qing Zhang; Hai Lou; Xiao-na Shen; Qing-rong Qu; Jie Cao; Wei Wei; Wei Sha; Qin Sun (BMC, 2023)
Abstract Objective To evaluate the effectiveness and safety of linezolid-containing regimens for treatment of M. abscessus pulmonary disease. Methods The records of 336 patients with M. abscessus pulmonary disease who were admitted to Shanghai Pulmonary Hospital from January 2018 to December 2020 were retrospectively analyzed. A total of 164 patients received a linezolid-containing regimen and 172 controls did not. The effectiveness, safety, antibiotic susceptibility profiles, outcomes, culture conversion, cavity closure, and adverse reactions were compared in these two groups. Results The two groups had similar treatment success (56.1% vs. 48.8%; P > 0.05), but treatment duration was shorter in the linezolid group (16.0 months [inter-quartile ranges, IQR: 15.0-17.0] vs. 18.0 months [IQR: 16.0-18.0]; P < 0.01). The rates of sputum culture conversion were similar (53.7% vs. 46.5%, P > 0.05), but time to conversion was shorter in the linezolid group (3.5 months [IQR: 2.5-4.4] vs. 5.5 months [IQR: 4.0-6.8]; P < 0.01). The linezolid group had a higher rate of cavity closure (55.2% vs. 28.6%, P < 0.05) and a shorter time to cavity closure (3.5 months [IQR: 2.5-4.4] vs. 5.5 months [IQR: 4.0-6.8]; P < 0.01). Anemia and peripheral neuropathy were more common in the linezolid group (17.7% vs. 1.7%, P < 0.01; 12.8% vs. 0.6%, P < 0.01). Conclusions The linezolid and control groups had similar treatment success rates. The linezolid group had a shorter treatment duration, shorter time to sputum culture conversion, and higher rate and shorter time to lung cavity closure. More patients receiving linezolid developed anemia and peripheral neuropathy.